PENERJEMAHAN NOMINA BAHASA INGGRIS PADA NOVEL THE PENDERWICKS KARYA JEANNE BIRDSALL KE DALAM BAHASA INDONESIA - TERWELINE TAPILATU (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2014)
This research, which is a qualitative one, aims at describing how nouns in the novel ThePenderwicks are translated into Indonesian and how the procedures used in translating thenouns affect the equivalence between the source and target texts as well as the acceptabilityand naturalness of the target text. The data were collected from two documents, i.e. theEnglish novel The Penderwicks: a Summer Tale of Four Sisters, Two Rabbits, and a VeryInteresting Boy by Jeanne Birdsall and its translation ‘Keluarga Penderwick: Kisah MusimPanas Empat Kakak-Beradik Perempuan, Dua Kelinci, dan Seorang Anak Laki-Laki yangMenarik’ in Indonesian, and were analised using the content analysis method.The findings show that the English nouns were translated into different forms andmeanings by using eight procedures i.e. shifts, modulation, contextual conditioning,naturalisation, transference (borrowing), translation by omission, translation by paraphraseusing a related word, and translation by paraphrase using unrelated words. The purposes forapplying these various procedures are mainly to bridge the differences between bothlanguages including their cultures, produce natural equivalents in the target text, adjust thecontext of utterance in the source text into the target one, overcome the lack of vocabulary inthe target text, produce effective sentences, and clarify the source text meaning. The use ofsome of these procedures has resulted in the shift of meaning but there is no significantdistortion of meaning. The translation text is generally intelligible, acceptable, natural andconsidered appropriate for its intended readers, i.e. children